Aspekte Van Die Gesondheidsvoorligtingstaak Van Die Gemeenskapgesondheidsverpleegster - E. Grobbelaar (AOSIS, 1979)
Health education is never-ending. It should be basic to the philosophy of the health worker and especially of the community health nurse. She stands at the heart of the community, knows the people and therefore bears a heavy responsibility to inspire them, help them to gain insight and lead them to take initiative. The success of her work as a whole will be measured by her guidance of the community as such to accept and experience as a way of life the promotion of health at all levels.